Multilocus Analysis of matK, atpB-rbcL Intergenic Spacer, and trnL-trnF Intergenic Spacer in Pandanaceae - Putri, Fatma Jumaita; Herman, Herman; Roslim, Dewi Indriyani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Species within the Pandanaceae family, particularly those in the Pandanus genus, exhibit substantial morphological variation, often leading to challenges in accurate species identification. This study conducted a multilocus DNA barcode analysis using sequences of matK, atpB-rbcL Intergenic Spacer (IGS), and trnL-trnF Intergenic Spacer (IGS) obtained from GenBank. Sequence alignment was performed using MAFFT v.7, and the aligned sequences were concatenated into multilocus datasets. Further analyses included frequency data evaluation and phylogenetic tree construction using the Neighbor Joining method in MEGA11. Results revealed that matK had the highest number of conserved sites and the greatest genetic stability, making it particularly effective for identifying broader taxonomic groups. In contrast, atpB-rbcL IGS and trnL-trnF IGS showed greater genetic variation, useful for distinguishing species with similar morphological features. Phylogenetic trees based on single- or two-locus data often failed to group species accurately, while multilocus combinations yielded well-resolved and more reliable tree structures. Therefore, the combined use of atpB-rbcL IGS + matK + trnL-trnF IGS significantly improves species resolution and reduces taxonomic misidentification within Pandanaceae. This study underscores the importance of multilocus barcoding in addressing limitations of morphological classification and enhancing molecular taxonomy in morphologically complex plant groups.